Polycarbonate having electro-optical effect, method for producing the same, and light control element using the same
By developing non-crosslinked polycarbonate, using parts with electro-optical characteristics and specific structural units, the shortcomings of existing electro-optical materials in high speed and high temperature stability are solved, and high EO effect and long-term high temperature stability are achieved, which is suitable for the next generation of ultra-high speed optical communication.
Patent Information
- Application Number
- CN201980016326.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-02
- Filing Date
- 2019-03-01
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2039-03-01
AI Technical Summary
Existing inorganic electro-optical materials have limits in terms of high speed and are difficult to meet the needs of next-generation ultra-high-speed optical communications. At the same time, there is a long-term high-temperature stability problem with the EO effect during the device manufacturing process of optical control components.
A non-crosslinkable polycarbonate is developed to contain parts with electro-optical properties and to improve its glass transition temperature and mechanical properties through specific structural units and manufacturing methods to achieve high EO effects and long-term high temperature stability.
It realizes the high transparency of polycarbonate in the O-band and C-band of optical communication, improves the intensity and long-term high-temperature stability of optical control elements, and is suitable for the next generation of ultra-high-speed optical communication.
Smart Images

Figure CN111868612B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polycarbonate having an electro-optical effect, a method for producing the same, and a light control element using the polycarbonate. Background Art
[0002] So far, inorganic materials such as lithium niobate have been used for electro-optical materials that can be used for optical modulators, optical switches, optical memories, optoelectronic circuits, wavelength conversion, electric field sensors, THz (Terahertz) wave generators and receivers, holograms and other optical control elements. However, such inorganic materials have limitations in terms of high speed and are still not satisfactory for realizing the next generation of ultra-high-speed optical communications.
[0003] For the above situation, since organic electro-optic polymer (hereinafter, also referred to as "EO polymer") shows a larger electro-optic effect (hereinafter, also referred to as "EO effect") compared with inorganic materials, it can be operated at high speed, so it can be expected to be an electro-optic material for the next generation of optical communication. However, there are many problems to be solved in the device manufacturing process of the light control element, which has not yet reached practical application. As this problem, the long-term high temperature stability of the EO effect can be cited.
[0004] Regarding this issue, Patent Document 1 discloses a crosslinkable polymer composition of a polymer containing a site having electro-optical properties (hereinafter, also referred to as "EO site") in the side chain. In the invention described in Patent Document 1, by making the polymer crosslinkable, the activity of the EO site is restricted, and a high glass transition temperature can be obtained. Thus, the crosslinkable polymer composition described in Patent Document 1 can provide a high EO effect and long-term high temperature stability of the effect.
[0005] Patent Document 2 discloses an acrylic EO polymer using a specific acrylic monomer. Such an acrylic EO polymer has a high glass transition temperature and can maintain the orientation of the EO site obtained after polarization treatment for a long time, thereby achieving long-term high-temperature stability of the EO effect.
[0006] Electro-optical molecules are disclosed in, for example, Patent Documents 3 to 5 and Non-Patent Documents 1 to 4.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2014-44272
[0010] Patent Document 2: Japanese Patent Application Publication No. 2015-178544
[0011] Patent Document 3: U.S. Patent No. 6067186
[0012] Patent Document 4: Japanese Patent Application No. 2004-501159
[0013] Patent Document 5: International Publication No. 2011 / 024774A1
[0014] [Non-patent literature]
[0015] Non-patent document 1: Toshiki Yamada, et al., "Effect of two methoxy groups bound to an amino-benzene donor unit for thienyl-di-vinylene bridged EOchromophores, Optical Materials, June 25 2013, volume 35, issue 12, page 2194-2200
[0016] Non-patent document 2: Toshiki Yamada, et al., "Important role of the ethylenedioxy group bound to the thienyl-di-vinyleneπ-conjugation unit oftricyanofuran-based donor-acceptor electro-optic chromophores", OpticalMaterials Express, 1September 2016, Volume 6, No.9, page 3021-3035
[0017] Non-patent document 3: Toshiki Yamada, et al., "Effect of methoxy or benzyloxygroups bound to an amino-benzene donor unit for various nonlinear opticalchromophores as studied by hyper-Rayleigh scattering", Materials Chemistry and Physics, 15May 2013, Volume 139, issues 2-3, page 699-705
[0018] Non-patent document 4: Mingqian He, et al., "α-Hydroxy Ketone Precursors Leading to a Nobel class of Electro-optic Acceptors", Chemistry of Materials, 17April2002, Volume 14, pages 2393-2400. Summary of the invention
[0019] The present invention aims to provide a novel polymer having an electro-optical effect, and also aims to provide a method for producing such a polymer and a light control element using such a polymer.
[0020] The present inventors have found that the above-mentioned problems can be solved by the present invention having the following aspects.
[0021] Method 1
[0022] A non-crosslinked polycarbonate containing sites with electro-optical properties.
[0023] Method 2
[0024] The polycarbonate according to Embodiment 1, comprising a structural unit of the following formula (1):
[0025]
[0026] (In the formula, R1 to R4 are each independently selected from a hydrogen atom, a halogen atom, and a straight-chain or cyclic, substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms which may have heteroatoms and / or branches; X is selected from a single bond, a sulfur atom, an oxygen atom, and a straight-chain or cyclic, substituted or unsubstituted divalent hydrocarbon group having 1 to 30 carbon atoms which may have heteroatoms and / or branches).
[0027] Method 3
[0028] The polycarbonate according to Embodiment 2, wherein X comprises the following formula (2):
[0029]
[0030] (wherein, at least one of R5 and R6 is selected from a halogen atom and a straight-chain or cyclic, substituted or unsubstituted hydrocarbon group having 2 to 20 carbon atoms which may have a hetero atom and / or may have a branch, and the other is selected from a hydrogen atom, a halogen atom and a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms which may have a hetero atom and / or may have a branch; or
[0031] R5 and R6 are bonded to form a substituted or unsubstituted cyclic hydrocarbon group having 4 to 20 carbon atoms, which may have a hetero atom and / or may have a branch).
[0032] Method 4
[0033] The polycarbonate according to Embodiment 3, wherein R5 and R6 are bonded to form a cyclic group having 1 to 5 substituents, the substituents are independently selected from alkyl groups having 1 to 4 carbon atoms, and the cyclic group is selected from cyclic alkyl groups or aryl groups.
[0034] Method 5
[0035] The polycarbonate according to any one of aspects 1 to 4, wherein the weight average molecular weight is 20,000 or more.
[0036] Method 6
[0037] The polycarbonate according to any one of aspects 1 to 5, wherein the glass transition temperature is 120° C. or higher.
[0038] Method 7
[0039] The polycarbonate according to any one of aspects 1 to 6, wherein the site having electro-optical properties comprises an electron-donating donor structure portion, an electron-accepting acceptor structure portion, and a conjugated bridging structure portion connecting the donor structure portion and the acceptor structure portion.
[0040] Method 8
[0041] A method for producing polycarbonate comprises the following steps: reacting a bisphenol compound, a diol compound having electro-optical properties and phosgene in the presence of an acid-binding agent and a solvent.
[0042] Method 9
[0043] The production method according to Embodiment 8, wherein the acid binding agent is pyridine.
[0044] Method 10
[0045] The production method according to embodiment 8 or 9, wherein a terminal blocking agent is further reacted in the above reaction.
[0046] Method 11
[0047] The production method according to any one of Embodiments 8 to 10, wherein the reaction is performed at a temperature of 35° C. or lower.
[0048] Method 12
[0049] A light control element comprising the polycarbonate according to any one of aspects 1 to 7.
[0050] Method 13
[0051] An optical waveguide is formed from the polycarbonate according to any one of aspects 1 to 7. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The structure of an optical waveguide as one form of an optical control element is exemplified. DETAILED DESCRIPTION
[0053] Polycarbonate
[0054] The polycarbonate of the present invention contains an EO moiety and is non-crosslinked.
[0055] In this specification, "non-crosslinkable polymer" is used in a different meaning from the crosslinkable polymer described in Patent Document 1, and for example, means that the crosslinkable functional group in the polymer is 10 mol%, 5 mol% or less, 3 mol% or less, 1 mol% or less, 0.5 mol% or less, 0.3 mol% or less, or 0.1 mol% or less.
[0056] The inventors of the present invention have found that by introducing molecules with electro-optical properties into polycarbonate, it is possible to have both a high EO effect and the long-term high temperature stability of the effect. In addition, it was found that in the cross-linked polymer composition described in Patent Document 1 and the acrylic EO polymer described in Patent Document 2, if a film is formed on a substrate and the film is peeled off from the substrate, the film will be relatively easy to break, and there are problems in terms of strength when used in devices, but if it is the polycarbonate of the present invention, such problems can be solved. In addition, it is known that the polycarbonate of the present invention has high transparency to near-infrared light in the O band (1260nm~1360nm) and C band (1530nm~1565nm) used for optical communication, which is very useful for optical control elements.
[0057] The polycarbonate of the present invention can have a high glass transition temperature, for example, the glass transition temperature can be 100°C or more, 110°C or more, 120°C or more, 130°C or more, 140°C or more, 150°C or more, 160°C or more, 170°C or more, 180°C or more, or 190°C or less, 250°C or less, 230°C or less, 210°C or less, or 190°C or less. For example, the glass transition temperature can be 100°C to 250°C, 120°C to 230°C, or 170°C to 210°C. By having a glass transition temperature in such a range, long-term high temperature stability of the EO effect can be obtained, and thermal decomposition of the EO site can be prevented during polarization treatment.
[0058] 〈Polymer Structure〉
[0059] The polycarbonate of the present invention may have a weight average molecular weight (Mw) of 10,000 or more, 15,000 or more, 18,000 or more, 20,000 or more, 25,000 or more, 30,000 or more, 35,000 or more, 40,000 or more, 45,000 or more, or 50,000 or less, or 300,000 or less, or 200,000 or less, or 150,000 or less, or 100,000 or less, when measured by GPC method using chloroform as solvent and based on standard polystyrene. For example, the weight average molecular weight (Mw) may be 15,000 to 300,000 or 40,000 to 200,000. In addition, the molecular weight distribution (Mw / Mn) can be 1.5 or more, 2.0 or more, 2.5 or more, 3.0 or more, 3.5 or more, 4.0 or more, 4.5 or more, or 5.0 or less, 10.0 or less, 8.0 or less, 7.0 or less, or 6.0 or less. For example, the molecular weight distribution (Mw / Mn) can be 1.5 to 10.0 or 3.0 to 8.0. If it is within such a range, sufficient strength and sufficient processability can be provided.
[0060] (Main component unit)
[0061] The polycarbonate of the present invention is not particularly limited as long as it contains main structural units linked by carbonate groups in the main chain and is within the range where the above-mentioned advantageous effects of the present invention can be obtained.
[0062] Examples of such structural units include structural units derived from bisphenol compounds, for example, structural units of the following formula (1):
[0063]
[0064] (In the formula, R1 to R4 are each independently selected from a hydrogen atom, a halogen atom, and a straight-chain or cyclic, substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms which may have heteroatoms and / or branches; X is selected from a single bond, a sulfur atom, an oxygen atom, and a straight-chain or cyclic, substituted or unsubstituted divalent hydrocarbon group having 1 to 30 carbon atoms which may have heteroatoms and / or branches).
[0065] In the formula (1), preferably, R1 to R4 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 5 to 20 carbon atoms, a cycloalkyloxy group having 6 to 20 carbon atoms, an aryl group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, or an aralkyloxy group having 7 to 20 carbon atoms. X is a single bond, a substituted or unsubstituted alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted alkylidene group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, a substituted or unsubstituted cyclic alkyl group having 3 to 8 carbon atoms, a sulfur atom, or an oxygen atom.
[0066] Preferably, in the structural unit represented by the above formula (1), R1 to R4 are each independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, or an aryl group having 6 to 10 carbon atoms.
[0067] Preferably, in the above formula (1), X is a substituted or unsubstituted divalent cyclic hydrocarbon group having 5 to 30 carbon atoms which may have a heteroatom and / or may have a branch, or a substituted or unsubstituted divalent linear hydrocarbon group having 1 to 30 carbon atoms which may have a heteroatom and contains a cyclic group in the branched portion.
[0068] More preferably, in the above formula (1), X comprises the following formula (2):
[0069]
[0070] (wherein, at least one of R5 and R6 is selected from a halogen atom and a straight-chain or cyclic, substituted or unsubstituted hydrocarbon group having 2 to 20 carbon atoms which may have a hetero atom and / or may have a branch, and the other is selected from a hydrogen atom, a halogen atom and a substituted or unsubstituted hydrocarbon group having 1 to 20 carbon atoms which may have a hetero atom and / or may have a branch; or
[0071] R5 and R6 are bonded to form a substituted or unsubstituted cyclic hydrocarbon group having 4 to 20 carbon atoms which may have a hetero atom and / or may have a branch).
[0072] It is further preferred that at least one of R5 and R6 contains a substituted or unsubstituted cyclic hydrocarbon group having 4 to 20 carbon atoms which may have a heteroatom and / or may have a branch, or that R5 and R6 are bonded to form the cyclic hydrocarbon group.
[0073] It is particularly preferred that R5 and R6 are bonded to each other to form a cyclic group having 1 to 5 substituents, wherein the substituents are independently selected from alkyl groups having 1 to 4 carbon atoms, and the cyclic group is selected from cyclic alkyl groups or aryl groups.
[0074] By selecting X with a large volume in this way, there is a tendency to increase the glass transition temperature of polycarbonate. In addition, there is a tendency to increase the γ dispersion temperature of polycarbonate, that is, the temperature at which rotation around the axial direction of the main chain starts. The present inventors have found that in addition to the glass transition temperature, the γ dispersion temperature also affects the long-term high temperature stability when the polycarbonate-based EO polymer is used in a light control element, and found that it is preferable to select X as described above. On the other hand, the present inventors have also found that when the volume of X is too large, the transparency of the polymer to near-infrared light in the wavelength bands of the O band (1260nm~1360nm) and the C band (1530nm~1565nm) used for optical communication is reduced, and found that it is preferable to select X in the range described above.
[0075] It should be noted that, in this specification, "substituted" means substituted by a hydrocarbon group having 1 to 15 carbon atoms, which may have a hetero atom and / or may have a branched linear or cyclic group, unless otherwise specified. In this case, the substituent may be present in plural. In addition, "hetero atom" may specifically include oxygen atoms and sulfur atoms.
[0076] In order to introduce the above-mentioned structural unit, a bisphenol compound can be used, and in particular, a bisphenol compound of the following formula (3) can be used:
[0077]
[0078] (wherein, R1 to R4 and X are as described above, and preferred R1 to R4 and X are also as described above).
[0079] Specifically, the following bisphenol compounds can be used: 1,1-bis-(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (hereinafter referred to as bisphenol TMC), 2,2-bis(4-hydroxyphenyl)propane (hereinafter referred to as bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3-isopropylphenyl)propane, 2,2-bis(3-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3-phenyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-diisopropyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-di-tert-butyl-4-hydroxyphenyl)propane, 2,2-bis(3,5-diphenyl-4-hydroxyphenyl)propane, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-isopropylphenyl)cyclohexane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(3-phenyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(3,5-dimethyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(3,5-diisopropyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(3,5-di-tert-butyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(3,5-diphenyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxy-2,3,5,6-tetramethylphenyl)cyclohexane, 1,1 -Bis(4-hydroxy-3-methylphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(3-tert-butyl-4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(3-phenyl-4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(3,5-dimethyl-4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(3,5-diisopropyl-4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(3,5-di-tert-butyl-4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(3,5-diphenyl-4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxy-2 ,3,5,6-tetramethylphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxy-3,3'-dimethyl-1,1-biphenyl, 4,4'-dihydroxy-3,3'-dioctyl-1,1-biphenyl, 1,3-bis(2-(4-hydroxy-3-methylphenyl)-2-propyl)benzene, 1,4-bis(2-(4-hydroxy-3-methylphenyl)-2-propyl)benzene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 4,4'-dihydroxy-3,3'-dimethyl diphenyl ether, 3,3'-dimethyl-4,4'-dihydroxy diphenyl sulfide, bis(4-hydroxy-2,6-dimethyl-3-methoxyphenyl)methane, 2,2-bis(4-hydroxy-3-ethylphenyl)propane, 1,1-bis(3-methyl-4-hydroxyphenyl)decane, 1,1-bis(2,3-dimethyl-4-hydroxyphenyl)decane.
[0080] Among them, bisphenol TMC represented by the following formula (4) is particularly preferred:
[0081]
[0082] Since the part corresponding to the X connecting two phenols is a cyclic group and there are multiple substituents on the cyclic group, the molecular activity of bisphenol TMC is greatly restricted. As a result, a high glass transition temperature and a high γ dispersion temperature can be given to polycarbonate, which is particularly useful in the use of light control elements. Bisphenol compounds with a large volume corresponding to the part of X are also useful like bisphenol TMC.
[0083] The polycarbonate of the present invention may contain constituent units derived from bisphenol compounds at 50 mol% or more, 55 mol% or more, 60 mol% or more, 65 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, or 90 mol% or less, 95 mol% or less, 90 mol% or less, 85 mol% or less, 80 mol% or less, 75 mol% or less, or 70 mol% or less. For example, the polycarbonate of the present invention may contain constituent units derived from bisphenol compounds at 50 mol% to 99 mol% or 70 mol% to 90 mol%. If it is within such a range, there is a tendency that the strength and EO effect of the obtained polycarbonate become sufficient. Here, the molar ratio may be a molar ratio theoretically derived from the raw materials used, and can be calculated from the peak area ratio of the characteristic spectrum of each constituent unit by dissolving 40 mg of polycarbonate in 0.6 ml of deuterated chloroform solution and measuring 1H-NMR using a 400 MHz nuclear magnetic resonance apparatus manufactured by JEOL Ltd.
[0084] (Parts with electro-optical properties)
[0085] The EO site contained in the polycarbonate of the present invention may be bonded as a pendant group to a functional group of a side chain of a polymer after polymerization, or may be bonded to a polymer as a part of a copolymer by using a precursor compound of the site as a monomer.
[0086] The type of the EO site is not particularly limited as long as the polymer to which it is bonded is heated to a temperature above the glass transition temperature and an electric field is applied to align the site in the direction of the electric field, and then the site is cooled to a temperature below the glass transition temperature (so-called polarization treatment) to maintain the alignment.
[0087] In order to avoid decomposition under heating during polarization treatment, the decomposition temperature of the EO part contained in the polymer of the present invention may be 120°C or more, 140°C or more, 160°C or more, 180°C or more, 200°C or more, or 300°C or less, 250°C or less, 230°C or less, or 200°C or less. The decomposition temperature may be 120°C to 300°C or 140°C to 250°C.
[0088] The molar ratio of the EO part contained in the polymer of the present invention may be 1 mol% or more, 3 mol% or more, 5 mol% or more, 8 mol% or more, 10 mol% or more, 15 mol% or more, or 20 mol% or more, or 50 mol% or less, 40 mol% or less, 30 mol% or less, 25 mol% or less, 20 mol% or less, 15 mol% or less, or 10 mol% or less. The molar ratio of the EO part may be 1 mol% to 50 mol% or 10 mol% to 30 mol%. Alternatively, as the weight ratio of the EO part, it may be 1 wt% or more, 3 wt% or more, 5 wt% or more, 8 wt% or more, 10 wt% or more, 15 wt% or more, 20 wt% or more, 25 wt% or more, or 30 wt% or more, or 80 wt% or less, 65 wt% or less, 50 wt% or less, 45 wt% or less, 40 wt% or less, 35 wt% or less, or 30 wt% or less. The weight ratio of the EO part can be 1 wt% to 80 wt% or 20 wt% to 50 wt%. If it is within such a range, there is a tendency that the strength and EO effect of the obtained polycarbonate become sufficient. Here, the molar ratio and weight ratio can also be values theoretically derived from the raw materials used. 40 mg of polycarbonate can be dissolved in 0.6 ml of deuterated chloroform solution, and 1H-NMR can be measured using a 400 MHz nuclear magnetic resonance device made by JEOL, and the peak area ratio of the spectrum with characteristics of each constituent unit can be calculated.
[0089] The EO site may have an electron-donating donor structure D, an electron-accepting acceptor structure A, and a conjugated bridging structure P connecting the donor structure D and the acceptor structure A. In this case, the EO site may be bonded to the polymer via either the donor structure D or the acceptor structure A, but preferably the donor structure D.
[0090] As the donor structure part D, as long as it is bonded to the conjugated system bridge structure part P through a conjugated bond and has an electron-donating group, there is no particular limitation. The donor structure part D can be, for example, a substituted or unsubstituted conjugated cyclic group containing a portion bonded to the conjugated system bridge structure part P through a conjugated bond, a bonding portion to a polymer, and an electron-donating group. In this case, the portion bonded to the conjugated system bridge structure part P through a conjugated bond and the bonding portion to the polymer can be a part of the electron-donating group, respectively, or can also be a portion directly bonded to the conjugated cyclic group.
[0091] Examples of the conjugated cyclic group of the donor structure D include monocyclic or polycyclic cyclic hydrocarbon groups or heterocyclic groups having conjugated electrons in the ring, and particularly include aromatic rings or heteroaromatic rings.
[0092] The electron donating group of the donor structure D may be bonded to the conjugated cyclic group or may be included in the substituent of the conjugated cyclic group. Examples of the electron donating group include amino groups, particularly tertiary amino groups bonded to the conjugated cyclic group and constituting a part of the main chain of the polymer.
[0093] The donor structure D preferably contains aminobenzene, and particularly preferably contains aminobenzene having an alkoxy group.
[0094] The bridge structure P is not particularly limited as long as it connects the donor structure D and the acceptor structure A with a conjugated bond, and for example, it can be only a carbon-carbon conjugated bond. In addition, for example, the bridge structure P can be a part of a substituted or unsubstituted conjugated cyclic group including a part bonded to the donor structure D with a carbon-carbon conjugated bond and a part bonded to the acceptor structure A with a carbon-carbon conjugated bond. The bridge structure P preferably has a thienyl group, and particularly preferably has a thienylethylene structure.
[0095] As the acceptor structure part A, as long as it is bonded to the conjugated system bridge structure part P with a conjugated bond and has an electron-withdrawing group, there is no particular limitation. The acceptor structure part A can be, for example, a substituted or unsubstituted conjugated cyclic group or a conjugated straight-chain hydrocarbon group comprising a part bonded to the conjugated system bridge structure part P with a conjugated bond and an electron-withdrawing group. In this case, the part bonded to the conjugated system bridge structure part P with a conjugated bond can be a part directly bonded to the conjugated cyclic group or the conjugated straight-chain hydrocarbon group.
[0096] Examples of the conjugated cyclic group of the acceptor structure part A include monocyclic or polycyclic cyclic hydrocarbon groups or heterocyclic groups having conjugated electrons in the ring.
[0097] The electron withdrawing group of the acceptor structure part A may be bonded to a conjugated cyclic group or a conjugated straight-chain hydrocarbon group, or may be included in a substituent of a conjugated cyclic group. Examples of the electron withdrawing group include a nitrile group (-CN), a fluorinated carbon group (e.g., a trifluoromethyl group), and the like. It is preferred that a plurality of electron withdrawing groups exist in the acceptor structure part A.
[0098] The acceptor structure part A preferably contains a tricyanofuran derivative, and particularly preferably contains a tricyanofuran derivative containing a trifluoromethyl group.
[0099] Such an EO site can be obtained, for example, by bonding a molecule having second-order nonlinear optical properties as described in Patent Documents 3 to 5 and Non-Patent Documents 1 to 4 to a polymer.
[0100] In order to bond the EO site to the polymer during polymerization, a diol compound having electro-optical properties may be used as a monomer. For example, a diol compound having electro-optical properties may be used as a starting material when synthesizing the compound. For example, although in Example 66 of Patent Document 5, 4-butylamino-1-butanol is used as a starting material to ultimately obtain a monohydroxy compound having electro-optical properties, a diol compound having electro-optical properties may be obtained by using a diol as the starting material and appropriately changing the reaction conditions and reaction steps.
[0101] Specifically, examples of diol compounds having electro-optical properties include the following compounds:
[0102]
[0103] D, P and A described below the above formula represent a donor structure portion D, a conjugated bridging structure portion P and an acceptor structure portion A, respectively.
[0104] In order to bond the EO site to the polymer during polymerization, the trifunctional or higher compound described below can also be used as a monomer, and the monohydroxy compound having second-order nonlinear optical properties described in Patent Document 5, etc. can be reacted with the trifunctional or higher compound to introduce the monohydroxy reactant into the polycarbonate.
[0105] (Other components)
[0106] As structural units other than bisphenol compounds and electro-optical molecules, structural units derived from aliphatic diols can be cited, for example. Such aliphatic diols include, for example, isosorbide: 1,4:3,6-dianhydro-D-sorbitol, tricyclodecane dimethanol (TCDDM), 4,8-bis(hydroxymethyl)tricyclodecane, tetramethylcyclobutanediol (TMCBD), 2,2,4,4-tetramethylcyclobutane-1,3-diol, mixed isomers, cis / trans-1,4-cyclohexanedimethanol (CHDM), cis / trans-1,4-bis(hydroxymethyl)cyclohexane, 1,4 -cyclohexanedimethanol, trans-1,4-cyclohexanedimethanol (tCHDM), trans-1,4-bis(hydroxymethyl)cyclohexane, cis-1,4-cyclohexanedimethanol (cCHDM), cis-1,4-bis(hydroxymethyl)cyclohexane, cis-1,2-cyclohexanedimethanol, 1,1'-bis(cyclohexyl)-4,4'-diol, spirodiol, dicyclohexyl-4,4'-diol, 4,4'-dihydroxybicyclohexane and poly(ethylene glycol).
[0107] In addition, as other structural units, structural units derived from fatty acids can be cited. Therefore, the polycarbonate of the present invention can be polyester carbonate. As such fatty acids, for example, 1,10-dodecanedioic acid (DDDA), adipic acid, hexanedicarboxylic acid, isophthalic acid, 1,3-phthalic acid, terephthalic acid, 1,4-phthalic acid, 2,6-naphthalene dicarboxylic acid, 3-hydroxybenzoic acid (mHBA) and 4-hydroxybenzoic acid (pHBA) can be cited.
[0108] Furthermore, the polycarbonate of the present invention may contain a structural unit derived from polyorganosiloxane as necessary.
[0109] Furthermore, the polycarbonate of the present invention may contain constituent units derived from trifunctional or higher compounds as long as it is non-crosslinked, and may be a branched polycarbonate. Examples of trifunctional or higher compounds used in the branched polycarbonate include polyfunctional aromatic compounds, and specifically, preferred examples include triphenols such as 4,6-dimethyl-2,4,6-tris(4-hydroxydiphenyl)-2-heptene, 2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, and 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol. Among them, 1,1,1-tris(4-hydroxyphenyl)ethane is preferred.
[0110] It should be noted that the branched structural unit is not only derived from the polyfunctional compound but can also be generated by a side reaction occurring during the polymerization reaction by the melt transesterification method. The ratio of such a branched structure can be calculated by 1H-NMR measurement.
[0111] (Terminal Group)
[0112] The polycarbonate of the present invention is preferably blocked at its terminal. That is, the polycarbonate of the present invention preferably has terminal groups other than chloro or hydroxyl groups. By blocking the terminal of the polycarbonate of the present invention, mechanical properties and the like can be improved. For example, preferably, more than 50%, more than 60%, more than 70%, more than 80%, more than 90%, more than 95%, or more than 98% of the terminal groups of the polycarbonate of the present invention are blocked, i.e., are not chloro or hydroxyl groups.
[0113] For example, in order to provide such terminal groups, an end-capping agent may be used when the polycarbonate is polymerized. Examples of such end-capping agents include monofunctional phenol compounds, specifically, phenol, m-methylphenol, p-methylphenol, m-propylphenol, p-propylphenol, 1-phenylphenol, 2-phenylphenol, p-tert-butylphenol, p-cumylphenol, isooctylphenol, p-long-chain alkylphenol, etc. Such end-capping agents are particularly useful when the polycarbonate of the present invention is produced by a phosgene method.
[0114] 《Production method of polycarbonate》
[0115] The polycarbonate of the present invention may be produced by any method without particular limitation as long as a polymer capable of producing the advantageous effects of the present invention can be produced.
[0116] However, from the viewpoint of obtaining a high molecular weight polycarbonate, the polycarbonate of the present invention can be produced by a method comprising reacting the bisphenol compound, the diol compound having electro-optical properties, and phosgene in the presence of an acid binder and a solvent.
[0117] It should be noted that “a bisphenol compound, a diol compound having electro-optical properties and phosgene are reacted in the presence of an acid binder and a solvent” includes “a reaction product of a bisphenol compound and phosgene and a diol compound having electro-optical properties are reacted in the presence of an acid binder and a solvent” and “a bisphenol compound and a reaction product of a diol compound having electro-optical properties and phosgene are reacted in the presence of an amine compound as an acid binder and a solvent”.
[0118] As the acid binding agent, for example, alkali metal hydroxides such as sodium hydroxide and potassium hydroxide and amine compounds such as pyridine can be cited, among which pyridine can be used in particular. The amount of the acid binding agent, in particular the amount of the amine compound such as pyridine, can be 5 mass parts or more, 10 mass parts or more, or 15 mass parts or less, or 30 mass parts or less, or 20 mass parts or less, relative to 100 mass parts of the solvent.
[0119] Examples of the solvent include halogenated hydrocarbons such as dichloromethane, dichloroethane, and chlorobenzene. Among them, dichloromethane is particularly useful.
[0120] The amount of the monomer used can be 5 mass parts or more, 10 mass parts or more, or 15 mass parts or more, or 30 mass parts or less, or 20 mass parts or less, relative to 100 mass parts of the solvent. For example, the amount of the monomer can be used in an amount of 5 mass parts to 30 mass parts or 10 mass parts to 20 mass parts relative to 100 mass parts of the solvent.
[0121] The amount of phosgene may be 0.5 mol or more, 0.8 mol or more, 1.0 mol or more, 1.5 mol or more, or 3.0 mol or less, 2.0 mol or less, 1.8 mol or less, or 1.5 mol or less relative to 1 mol of the bisphenol compound. Within such a range, there is a tendency to obtain a polymer having a high molecular weight. For example, the amount of phosgene may be 0.5 mol to 3.0 mol or 0.8 mol to 2.0 mol relative to 1 mol of the bisphenol compound.
[0122] In addition, in the above-mentioned reaction, it is preferred to also react the end-capping agent as described above. The amount of the end-capping agent used can be 0.1 mass part or more, 0.3 mass part or more, 0.5 mass part or more, or 1.0 mass part or more relative to 100 mass parts of the monomer, or it can be 3 mass parts or less, 2 mass parts or less, 1 mass part or less, or 0.5 mass part or less. For example, the amount of the end-capping agent can be used in an amount of 0.1 mass part to 3 mass parts or 0.3 mass parts to 2 mass parts relative to 100 mass parts of the solvent.
[0123] The above reaction can be carried out at a temperature below 60°C, below 50°C, below 40°C, below 35°C, below 30°C, or below 25°C, and can be carried out at a temperature above 0°C, above 10°C, above 15°C, above 20°C, or above 25°C. For example, the reaction temperature can be 0°C to 60°C or 10°C to 50°C. In addition, the reaction time is not particularly limited as long as the residual monomer is sufficiently reduced and a high molecular weight polymer is obtained, and can be, for example, 30 minutes or more, 1 hour or more, 2 hours or more, or 3 hours or less, 10 hours or less, 5 hours or less, or 3 hours or less. For example, the reaction time can be 30 minutes to 10 hours or 1 hour to 5 hours.
[0124] The reaction may include: a first step of reacting the reaction mixture while blowing phosgene at a relatively low temperature, and a second step of stopping blowing phosgene and continuing the reaction at a relatively high temperature. For example, the first step may be carried out in a range of 0°C to 35°C, for example, 10°C to 30°C, and the second step may be carried out in a range of 20°C to 50°C, for example, 25°C to 35°C. In this case, the reaction temperature of the second step may be higher than the reaction temperature of the first step. These steps may be carried out for 10 minutes or more, 30 minutes or more, 1 hour or more, or 5 hours or less, 3 hours or less, 2 hours or less, or 1 hour or less, respectively.
[0125] The polycarbonate of the present invention can be produced by a transesterification reaction of a carbonate precursor, for example, a carbonic acid diester, with the above-mentioned bisphenol compound and a diol compound having electro-optical properties.
[0126] In this case, the reaction can be carried out by heating and stirring the above-mentioned bisphenol compound and the diol compound having electro-optical properties with a carbonic acid diester under an inert gas atmosphere, and distilling the generated alcohol or phenol compound under reduced pressure in the system. In this case, the reaction temperature varies depending on the boiling point of the generated alcohol or phenol compound, and is usually in the range of 120 to 300°C.
[0127] Examples of the carbonic acid diester include diphenyl carbonate, dinaphthyl carbonate, bis(diphenyl) carbonate, dimethyl carbonate, diethyl carbonate, and dibutyl carbonate. Among them, diphenyl carbonate can be particularly used.
[0128] In this reaction, a catalyst commonly used in transesterification reactions may be used. Alternatively, a terminal blocking agent as described above may be used.
[0129] 《Polycarbonate resin composition》
[0130] The polycarbonate of the present invention described above can be mixed with known functional agents such as a release agent, a heat stabilizer, an ultraviolet absorber, a flow improver, and an antistatic agent to use as a polycarbonate resin composition within a range not impairing the effects of the present invention.
[0131] Light Control Components
[0132] The light control element of the present invention contains at least the above-mentioned polycarbonate. The above-mentioned polycarbonate and polycarbonate resin composition can be preferably used as a material constituting the light control element due to their high EO effect, high long-term high-temperature stability of the effect, and high mechanical properties.
[0133] The optical control element of the present invention can be used in conventionally known methods, for example, for optical modulators, optical switches, multi-core switches, optical interconnectors, optical wiring in a chip, optical phased arrays, LiDAR (Light Detection And Ranging), electric field sensors, THz wave generators, THz sensors, high-sensitivity / high signal-to-noise ratio electroencephalographs, brain-computer interfaces (BMI), holographic imaging, etc. Among them, in particular, as the optical control element, an optical modulator or an optical switch can be cited.
[0134] For example, the light control element of the present invention may be Figure 1 A Mach-Zehnder optical waveguide as described. Figure 1 The optical waveguide 8 shown in FIG. 1 is stacked with a lower electrode 2, a lower cladding layer 3, a core layer 4, an upper cladding layer 5 and an upper electrode 6 in order from the substrate 1 side. The core layer 4 is subjected to polarization treatment and has an EO effect. The optical waveguide core 7 is formed by a reactive ion etching method or the like, and constitutes a Mach-Zehnder interferometer. When an electric field is applied by one of the lower electrode 2 and the upper electrode 6, or when electric fields in opposite directions are applied by two upper electrodes 6, the refractive index of the core layer 4 located between these electrodes changes, thereby changing the phase difference between the two arms of the Mach-Zehnder interferometer, and the intensity of the propagating light can be modulated.
[0135] Such a Mach-Zehnder optical waveguide can be produced by a known method described in Patent Document 1, for example.
[0136] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto.
[0137] Example
[0138] "Synthetic Example"
[0139] The diol compound having electro-optical properties represented by the following chemical formula (EO-1) is synthesized through steps 1 to 11 described below.
[0140]
[0141] <Synthesis Example - Step 1>
[0142] When step 1 is expressed as a reaction formula, it is as follows:
[0143]
[0144] Dissolve 18.35 g (0.175 mol) of diethanolamine (compound 1 in the formula) and 71.0 g (0.702 mol) of triethylamine in 500 ml of acetonitrile. Add 96.0 g (0.349 mol) of tert-butyldiphenylchlorosilane dropwise while stirring at room temperature and stir for 5 hours. Filter out the precipitated crystals, concentrate the filtrate and dry it. Extract the obtained white solid with 750 ml of hexane. Distill off the hexane to obtain 81.27 g of compound 2 as a colorless oil (solidified after standing at room temperature).
[0145] In addition, 24.86 g of the hexane insoluble portion was suspended in 200 ml of water, and then 200 ml of saturated sodium bicarbonate water and 300 ml of hexane were added and stirred (solid dissolution). The hexane layer was separated, dehydrated with anhydrous magnesium sulfate, and then concentrated to obtain 20.62 g of compound 2. A total of 101.89 g of compound 2 was obtained (crude yield 101.9%).
[0146] <Synthesis Example - Step 2>
[0147] Step 2 is represented by a reaction formula as follows:
[0148]
[0149] 75.5 g (0.13 mol) of compound 2 and 334.0 g (0.13 mol) of compound 3 ("1-benzyloxy-3-bromobenzene") were dissolved in 500 ml of dehydrated toluene, and 30.9 g (0.155 mol) of potassium bis(trimethylsilyl)amide was added while stirring at room temperature. After stirring for 2 hours in an oil bath at 110°C, the mixture was cooled and washed twice with saturated brine. The organic layer was dehydrated with anhydrous sodium sulfate and concentrated. 102.43 g of compound 4 (crude yield 103.7%) was obtained as an oil.
[0150] <Synthesis Example - Step 3>
[0151] Step 3 is represented by a reaction formula as follows:
[0152]
[0153] 102.43 g (0.134 mol) of compound 4 was dissolved in 250 ml of tetrahydrofuran, and 372 ml of tetrabutylammonium fluoride (1 mol tetrahydrofuran solution) was added dropwise while stirring at room temperature. After stirring for 30 minutes, it was poured into 1000 ml of water and extracted with ethyl acetate. After washing with saturated brine, it was dehydrated with anhydrous sodium sulfate and concentrated. After adding 500 ml of hexane to the residue and stirring, the hexane layer was removed by pouring. The remaining part after pouring was concentrated and purified by silica gel column chromatography (chloroform / methanol=10 / 1) to obtain 27.03 g of compound 5 (yield 72.8%) as a light yellow oil.
[0154] <Synthesis Example - Step 4>
[0155] When step 4 is expressed as a reaction formula, it is as follows:
[0156]
[0157] Add 40 ml of acetic anhydride to 27.03 g (0.094 mol) of compound 5, and stir in an oil bath at 100°C for 1 hour and 45 minutes. After cooling, add 300 ml of ether and 400 ml of water, and stir for 30 minutes. Separate the organic layer, and further extract the aqueous layer with 200 ml of ether. Combine the organic layers and wash them with saturated sodium bicarbonate aqueous solution, then wash them with saturated brine, and then dehydrate them with anhydrous magnesium sulfate and concentrate them. Purify the residual liquid by silica gel column chromatography (ethyl acetate / hexane=1 / 1). 31.75 g of compound 6 (yield 90.9%) was obtained as a light yellow oil.
[0158] <Synthesis Example - Step 5>
[0159] When step 5 is expressed as a reaction formula, it is as follows:
[0160]
[0161] 13.20 g (0.0861 mol) of phosphorus oxychloride was added dropwise to 80 ml of N,N-dimethylformamide while stirring under ice-cooling. After 20 minutes, the mixture was removed from the ice bath, heated to 12°C and stirred for 5 minutes. Ice-cooled again, 30.80 g (0.0829 mol) of compound 6 was dissolved in 40 ml of N,N-dimethylformamide and added dropwise. After stirring for 30 minutes, the mixture was slowly heated and stirred at 70°C for 2 hours. The reaction solution was cooled in an ice bath, while 180 ml of 20% sodium acetate aqueous solution was added dropwise and stirred for 40 minutes. The mixture was extracted twice with chloroform, and the extract was washed with saturated brine, saturated sodium bicarbonate aqueous solution, and saturated brine in sequence. After dehydration with anhydrous sodium sulfate, the residue was crystallized from ethanol and filtered. 28.0 g of compound 7 was obtained as colorless crystals with a melting point of 86-87°C. The filtrate was concentrated and purified by silica gel column chromatography (ethyl acetate / hexane=3 / 2) to obtain 2.70 g of compound 7. Thus, a total of 30.7 g (yield 92.7%) of compound 7 was obtained.
[0162] <Synthesis Example - Step 6>
[0163] When step 6 is expressed as a reaction formula, it is as follows:
[0164]
[0165] 28.29g (70.82mmol) of compound 7 was dissolved in 150ml of ethanol, 100ml of 7.4% sodium hydroxide aqueous solution was added dropwise thereto, and stirred at room temperature for 30 minutes. The reaction solution was injected into 600ml of saturated brine and extracted with chloroform. The extract was washed with saturated brine, dehydrated with anhydrous sodium sulfate and concentrated. The obtained powder was recrystallized using ethyl acetate to obtain 21.79g of compound 8 (yield 97.5%) in the form of white crystals with a melting point of 108-109°C.
[0166] <Synthesis Example - Step 7>
[0167] When step 7 is expressed as a reaction formula, it is as follows:
[0168]
[0169] Dissolve 21.78g (69.06mmol) of compound 8 and 21.6g (317.28mmol) of imidazole in 100ml of N,N-dimethylformamide. Add 39.0g (141.9mmol) of tert-butyldiphenylsilyl chloride dropwise while stirring at room temperature. After stirring for 40 minutes, add them to 400ml of water and extract with ethyl acetate. Wash the extract with saturated brine, dehydrate with anhydrous sodium sulfate and concentrate. Purify the residual liquid by silica gel column chromatography (ethyl acetate / hexane=2 / 5). Thus, 51.3g of compound 9 (yield 93.8%) was obtained as a light yellow oil.
[0170] <Synthesis Example - Step 8>
[0171] When step 8 is expressed as a reaction formula, it is as follows:
[0172]
[0173] Under argon flow, 27.6 ml (57.9 mmol) of phenyllithium (2.1 mol dibutyl ether solution) was added to 250 ml of tetrahydrofuran, and 20.8 g (52.7 mmol) of compound 10 ("2-thienyltriphenyl chloride") was added while stirring under ice cooling. ”). It should be noted that compound 10 was synthesized by the method described in Fig. 2(c) of non-patent document 3. After stirring for 10 minutes, 28.68 g (52.7 mmol) of compound 9 was made into 80 ml of tetrahydrofuran solution and added dropwise. After stirring for 2 hours under ice cooling, it was poured into 550 ml of water and extracted with ethyl acetate. After washing with saturated brine, it was dehydrated with anhydrous sodium sulfate and concentrated. To the residue was added 240 ml of ethyl acetate / hexane (1 / 5), stirred and then ice-cooled. After filtering out the precipitate, it was concentrated and the residual liquid was purified by silica gel column chromatography (ethyl acetate / hexane = 1 / 5) to obtain 30.18 g of compound 11-(Z / E) (yield 91.7%) as an orange oil.
[0174] <Synthesis Example - Step 9>
[0175] When step 9 is expressed as a reaction formula, it is as follows:
[0176]
[0177] Under an argon stream, 47.8 g (54.8 mmol) of compound 11-(Z / E) was dissolved in 320 ml of tetrahydrofuran, cooled in a dry ice / acetone bath, and 44.6 ml (71.4 mmol) of n-butyl lithium (1.6 mol hexane solution) was added dropwise. After stirring for 20 minutes, 4.47 g (61.2 mmol) of N,N-dimethylformamide was added dropwise. After stirring for 40 minutes, the mixture was removed from the dry ice / acetone bath and heated, and 20 ml of water was added dropwise. After stirring for 35 minutes, the mixture was poured into 600 ml of water and extracted with ethyl acetate. The extract was washed with saturated brine, dehydrated with anhydrous sodium sulfate, and concentrated. 49.63 g of the obtained dark red oil was dissolved in 800 ml of ether, and 1.5 g of iodine tablets were added thereto. After stirring at room temperature for 30 minutes, the mixture was washed twice with 200 ml of 5% sodium bisulfite aqueous solution. After further washing with saturated brine, the mixture was dehydrated with anhydrous magnesium sulfate and concentrated. The residue was purified by silica gel column chromatography (ethyl acetate / hexane = 1 / 3) to obtain 40.59 g of compound 12-(E) as a red oil (yield 82.3%).
[0178] <Synthesis Example - Step 10>
[0179] When step 10 is expressed as a reaction formula, it is as follows:
[0180]
[0181] Dissolve 38.0 g (42.2 mmol) of compound 12-(E) in 150 ml of tetrahydrofuran. Add 125 ml of tetrabutylammonium fluoride (1 mol tetrahydrofuran solution) dropwise while stirring at room temperature. After stirring for 30 minutes, inject into 500 ml of water and extract with 250 l of ethyl acetate. After washing the extract with saturated brine, dehydrate with anhydrous sodium sulfate and concentrate. Purify the residue by silica gel column chromatography (chloroform / methanol = 10 / 1). 17.08 g of the target compound 13-(E) (yield 95.6%) was obtained as a red oil.
[0182] <Synthesis Example - Step 11>
[0183] When step 11 is expressed as a reaction formula, it is as follows:
[0184]
[0185] 2.0 g (4.72 mmol) of compound 13-(E) and 1.64 g (5.20 mmol) of compound 14 ("2-(3-cyano-4-methyl-5-phenyl-5-trifluoromethyl-2(5H)-furanylidene)malononitrile") were dissolved in 18 ml of ethanol and 2 ml of tetrahydrofuran, heated to 50°C and stirred for 2 hours. It should be noted that compound 14 was synthesized by the method described in non-patent document 4. The reaction solution was ice-cooled, and the precipitated crystals were filtered and washed with ethanol. The obtained crystals were purified by silica gel column chromatography (chloroform / methanol = 10 / 1). Further washing with ethanol, 2.93 g of compound EO-1 (yield 86.2%) was obtained in the form of dark reddish brown crystals with a melting point of 153 to 156°C.
[0186] 《Production Example of Polymer》
[0187] <Example 1>
[0188] Into a 300 ml reaction container equipped with a thermometer, a stirrer and a reflux cooler, 12.89 parts by mass of pyridine and 69.22 parts by mass of dichloromethane as an acid binder and a solvent were respectively placed. 2.94 parts by mass of compound EO-1, 7.17 parts by mass of bisphenol TMC (produced by Honshu Chemical), and 0.05 parts by mass of p-tert-butylphenol as a terminal blocking agent were dissolved therein, and then 3.90 parts by mass of phosgene were blown in at 15 to 26°C for about 80 minutes while stirring. After the blowing of phosgene was completed, the reaction was terminated by stirring at 26 to 35°C for 60 minutes.
[0189] After the reaction, the product was diluted with dichloromethane and washed with water, and then hydrochloric acid was added to adjust the acidity and wash with water, and then the water washing was repeated until the conductivity of the aqueous phase was almost the same as that of ion exchange water, thereby obtaining a dichloromethane solution of polycarbonate. Next, the obtained dichloromethane solution was added dropwise to warm water maintained at 50 to 80°C, and the solvent was evaporated to obtain a flaky solid substance. The obtained solid substance was filtered and dried at 120°C for 24 hours to obtain 9.54 g of black flaky polycarbonate of Example 1.
[0190] <Example 2>
[0191] 5.03 g of a polycarbonate of Example 2 was obtained in the same manner as in Example 1 except that the amount of compound EO-1 was changed to 4.90 parts by mass and the amount of bisphenol TMC was changed to 6.33 parts by mass.
[0192] <Example 3>
[0193] 7.71 g of a polycarbonate of Example 3 was obtained in the same manner as in Example 1 except that 7.17 parts by mass of bisphenol TMC was changed to 6.33 parts by mass of bisphenol A.
[0194] <Example 4>
[0195] 3.22 g of the polycarbonate of Example 4 was obtained in the same manner as in Example 3 except that the amount of phosgene was changed to 1.44 parts by mass.
[0196] <Comparative Example 1>
[0197] Acrylic side chain EO polymer
[0198] In the same manner as in Example 57 of Patent Document 5, a monohydric alcohol compound having electro-optical properties represented by the following chemical formula (EO-2) was produced.
[0199]
[0200] Referring to Example 2 of Patent Document 2, an acrylic copolymer represented by the following chemical formula (AP-1) was produced.
[0201]
[0202] Here, n=3.92, m=1.
[0203] With reference to Example 12 of Patent Document 2, the copolymer is AP-1, the EO molecule is EO-2, the mixing ratio is adjusted so that the EO molecule concentration is 35 wt %, the OH group of the EO molecule reacts with the NCO group located in the side chain of AP-1, and the EO molecule is introduced as a side group, thereby producing an acrylic EO polymer.
[0204] <Comparative Example 2>
[0205] APEC Composite EO Polymer
[0206] In the same manner as in Example 6 of Patent Document 5, a compound having electro-optical properties represented by the following chemical formula (EO-3) was produced.
[0207]
[0208] Commercially available polycarbonate (Aldrich, 430587) and EO molecule EO-3 were mixed so that the EO molecule concentration was 20 wt %, and dissolved in cyclohexanone to prepare a composite EO polymer solution.
[0209] "evaluate"
[0210] <Measurement of weight average molecular weight Mw and molecular weight distribution Mw / Mn>
[0211] The molecular weight distribution Mw / Mn of the polycarbonate copolymer is determined by measuring the weight average molecular weight Mw and the number average molecular weight Mn by gel permeation chromatography (GPC) and using the polystyrene conversion method. The calibration curve is prepared using polystyrene standards with known molecular weights (12 types of Tosoh PS oligomer set A-500 to F-128). The measurement uses "HLC-8220GPC" manufactured by Tosoh, and the columns use three "TSK-gel SuperHZ4000 / 3000 / 2000" manufactured by Tosoh. The sample uses a solution obtained by dissolving 10 mg of the polycarbonate copolymer in 5 mL of chloroform (containing 0.05% internal standard toluene) and filtering it using "Millex LG4" manufactured by Millipore. The measurement is carried out under the conditions of 40°C and a flow rate of 0.35 mL / min. The eluent uses chloroform for high performance liquid chromatography manufactured by Wako Pure Chemical Industries, Ltd.
[0212] 〈EO site ratio〉
[0213] 40 mg of the polycarbonate copolymer was dissolved in 0.6 ml of a deuterated chloroform solution, and 1H-NMR was measured using a 400 MHz nuclear magnetic resonance apparatus manufactured by JEOL Ltd. The ratio of the EO site was calculated from the peak area ratio of the spectrum characteristic of each structural unit.
[0214] <Measurement of glass transition temperature (Tg)>
[0215] The Tg of the polymers obtained in Examples and Comparative Examples was measured using a differential scanning calorimeter (DSC-60A, manufactured by Shimadzu Corporation) with a measurement sample of 10 mg, an empty Al container as a standard sample, a nitrogen atmosphere, and a heating rate of 20°C / min.
[0216] 〈Electro-optic coefficient (r 33 ) determination method
[0217] A solution of each polymer dissolved in cyclohexanone at a concentration of 1 to 20 w% was applied to a glass substrate with an ITO film (GEOMATEC: 0008) having a film thickness of 9 nm using a spin coater (1H-DX2, manufactured by Mikasa Co., Ltd.) at 500 to 6000 rpm. Thereafter, the solution was vacuum dried at the glass transition temperature (Tg) for 1 hour using a vacuum constant temperature dryer (DRV220DC, manufactured by Advantec Toyo Co., Ltd.). The concentration of the polymer solution and the rotation speed of the spin coater were appropriately selected to achieve a desired film thickness of about 0.7 μm.
[0218] IZO was formed into a 100 nm thin film on the substrate with the polymer film and ITO film by magnetron sputtering. They were heated to a temperature near the glass transition temperature of the polymer, and a voltage was applied in the form of an electric field of 120 V / μm between ITO and IZO. After the voltage was kept for 5 minutes, it was cooled to room temperature and then the voltage was set to 0 V. Thus, the electro-optic coefficient (EO coefficient: r 33 ) Sample for measurement.
[0219] EO coefficient (r 33 ) was measured in the same manner as described in the reference paper (“Transmission ellipsometric method without an aperture for simple and reliable evaluation of electro-optic properties”, Toshiki Yamada and Akira Otomo, Optics Express, vol. 21, pages 29240-48 (2013). The laser light source used was DFB laser 81663A (wavelengths 1308 nm and 1550 nm) manufactured by Agilent Technologies.
[0220] 〈Evaluation of long-term high temperature stability〉
[0221] Determination of EO coefficient before heat treatment (r 33 ) and then placed in an oven at a high temperature (85°C). After 2000 hours, the sample was taken out and the electro-optic coefficient (r 33 ). According to the electro-optic coefficient (r 33 ) value to evaluate the long-term high temperature stability. In this case, the case where the EO coefficient after heat treatment can be maintained at 70% or more relative to 100% before heat treatment is evaluated as "0", the case where it can be maintained at 50% or more is evaluated as "△", and the case where it is maintained less than 50% is evaluated as "×".
[0222] 〈Evaluation of Strength〉
[0223] A polymer film was produced on a synthetic quartz substrate having a size of 25 mm×25 mm so as to have a film thickness of about 2 μm. The case where no cracks occurred was evaluated as “0”, and the case where cracks occurred was evaluated as “×”.
[0224] "result"
[0225] Table 1 summarizes the structures and evaluation results of Examples 1 to 4 and Comparative Examples 1 to 2.
[0226] [Table 1]
[0227]
[0228] *1 Bisphenol TMC
[0229] *2 Bisphenol A
[0230] Comparative Example 2, in which the EO moiety was added by compounding, showed poor long-term high temperature stability. Comparative Example 1, in which the EO moiety was introduced into the acrylic polymer by side chaining, showed high EO coefficient and glass transition temperature, but insufficient strength.
[0231] Explanation of symbols
[0232] 1 substrate
[0233] 2 Lower electrode
[0234] 3 lower cladding
[0235] 4 Core layer
[0236] 5 Upper cladding
[0237] 6 Upper electrode
[0238] 7 cores
[0239] 8 Optical waveguide
Claims
1. A non-crosslinked polycarbonate comprising a site having electro-optical properties, wherein the site having electro-optical properties comprises an electron-donating donor structure, an electron-accepting acceptor structure, and a conjugated bridging structure connecting the donor structure and the acceptor structure, wherein the donor structure comprises aminobenzene, the acceptor structure comprises a tricyanofuran derivative, and the conjugated bridging structure comprises a thienyl group, the weight average molecular weight of the polycarbonate is 20,000 or more, the weight ratio of the site having electro-optical properties is 25 wt % to 50 wt %, the site having electro-optical properties is bonded to a polymer as a part of a copolymer by using a precursor compound of the site having electro-optical properties as a monomer, and the structural unit other than the site having electro-optical properties is a structural unit derived from 1,1-bis-(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane or 2,2-bis(4-hydroxyphenyl)propane.
2. The polycarbonate according to claim 1, wherein The glass transition temperature is 120°C or higher.
3. A method for producing a polycarbonate according to claim 1 or 2, comprising the step of reacting a bisphenol compound, a diol compound having electro-optical properties and phosgene in the presence of an acid-binding agent and a solvent.
4. The manufacturing method according to claim 3, wherein: The acid binding agent is pyridine.
5. The manufacturing method according to claim 3 or 4, wherein: In the reaction, a capping agent is further reacted.
6. The manufacturing method according to claim 3 or 4, wherein: The reaction was carried out at a temperature below 35°C.
7. A light control element comprising the polycarbonate according to claim 1 or 2.
8. An optical waveguide formed from the polycarbonate according to claim 1 or 2.
Citation Information
Patent Citations
Novel Chromophores for Polymer Thin Films and Optical Waveguides and Devices Comprising the Same
JP2004501159A
Optical waveguide and production method of the same
JP2014044272A
Copolymer which is useful as organic electro-optic polymer and adjustable in glass transition temperature and organic electro-optic element using the same
JP2015178544A
Class of high hyperpolarizability organic chromophores and process for synthesizing the same
US6067186A
Second-order non-linear optical compound and non-linear optical element comprising same
WO2011024774A1